Sad hearts in heart failure patients - Middlemost, Shirley (SA Heart Journal, 2017)
Heart failure is a common clinical entity. Because patients with heart failure face high rates of debilitation and mortality, the study of depression characteristics in this population is a critical research area in the pursuit of improved quantity and quality of their lives. Studies have shown that depression is common in heart failure and, interestingly, that both conditions share similar pathobiological mechanisms. Depression in heart failure is a serious co-morbidity. It is a strong predictor of short-term worsening of heart failure symptoms, a decline in health status, mortality and re-hospitalization, independent of baseline ventricular function and severity of cardiovascular disease. Depression remains poorly recognized and under-treated in heart failure. The presence of depression is not random. It is disproportionately diagnosed amongst patients who are female, those suffering more advanced disease, those who are socially isolated and those of low socioeconomic status. Patients should be screened regularly for symptoms of depression. Although effective treatment is available, no studies have been done to show that treatment of depression has a positive impact on heart failure outcome.